PTU-069 The fate of epithelial keratins in active ulcerative colitis. (22nd June 2015) - Assad-Sangabi, A; Evans, C; Majumdar, D; Cross, SS; Corfe, BM; Lobo, AJ
Abstract : Introduction: Intermediate filaments (IF), which mainly consist of keratins (K), are one of the main components of the human cell cytoskeleton. K8, K18 and K19 constitute the main keratins in the intestinal epithelial cells. Keratin alterations may play a role in the pathophysiology of ulcerative colitis (UC). We have previously shown reduced expression of Keratins in IF fraction from distal active UC relative to proximal inactive mucosa as well as controls using proteomic iTRAQ-based analysis. 1 Whether this reduced expression is due to change in solubilisation, reduced total expression and/or degradation, is unknown. We aimed to clarify the fate of epithelial keratins during UC disease activity. Method: Soluble proteome fractions were extracted from rectal biopsies in patients (n = 10) with active distal colitis (ACT) as well as endoscopically and histologically uninflamed proximal colonic mucosa (INACT) in the same patients. Median histological activity index in ACT and INACT were 2 (range 1–3) and 0 (range 0). Control colonic biopsies (n = 7) from normal individuals were fractionated similarly. An iTRAQ-compatible extraction protocol for soluble proteins was developed and applied. Labelled peptides from pooled patients in each group were analysed by SCX-LC-MS/MS and data reconstituted in GeneBio Phenyx. Inter-group comparisons were made using in-house algorithms based on t-testing with multiple test correction. Validation of iTRAQ results was carried out with immunoblotting on pooled and individual samples using monoclonal antibody against K8. These outcomes were then compared with our previous insoluble proteome analyses. 1 Results: Comparative iTRAQ analysis of the soluble fraction showed significantly lower log fold changes in K8, K18 and K19 levels in ACT relative to INACT (0.42, 0.53, 0.42) and normal controls (0.61, 0.76, 0.41), respectively. The results were similar to our recent iTRAQ analysis of the IF fraction. 1 Immunoblotting further confirmed these findings: median relative K8 concentration in IF/soluble proteome fractions in individual ACT and INACT samples was 0.18/1 (p = 0.02) and 1.21/1.02 (p = 0.02), respectively. Conclusion: This study suggests relative total reduction in expression of epithelial keratins in actively inflamed colonic mucosa of UC patients compared to un-inflamed proximal mucosa and normal controls. Keratins may have utility as a tissue biomarker of UC disease activity. Disclosure of interest: None Declared. Reference: Corfe BM, Majumdar D, Assadsangabi A, Marsh AMR, Cross SS, Connolly JB, Evans CA, Lobo AJ. Inflammation decreases keratin level in ulcerative colitis; inadequate restoration associates with increased risk of colitis-associated-cancer. BMJ Open Gastroenterol., In press